The impact of globalization on traditional culture and values of modern Arab society - Amanzhol . S. Т. (Journal of Oriental Studies, 2024)
The article deals with the problems of the changes in traditional culture and values of modern Arab society in the process of globalization, particularly in religion, language, etiquette, clothing and food. Current global changes in the world and a new period of mankind have an impact on the development of the states in the world including Arab countries. Globalization is reflected in economic development, social status, education, culture, moral and religious spheres of Arab countries.